Polymorphisms Gly322Asp hMSH2 and Arg399Gln XRCC1 of the DNA repair system in breast cancer - Smolarz, Beata; Romanowicz-Makowska, Hanna; Makowski, Marcin; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2008)
Aim of the study: In the present work the distribution of genotypes and frequency of alleles of Gly322Asp hMSH2 gene and Arg399Gln XRCC1 gene polymorphism in subjects with breast cancer were investigated. Material and methods: Blood was obtained from 150 women with breast cancer and controls (n=129). The polymorphisms were determined by PCR-RFLP. Results: The distribution of the genotypes of the Arg399Gln polymorphism of XRCC1 and Gly322Asp polymorphism of hMSH2 in both controls and patients did not differ significantly (p>0.05) from those predicted by the Hardy-Weinberg distribution. There were no significant differences (p>0.05) in genotype distributions and allele frequencies between subgroups assigned to histological stage. Conclusions: The results suggest that the Arg399Gln polymorphism of the XRCC1 gene as well as the Gly322Asp polymorphism in hMSH2 may not be linked with appearance and development of breast cancer.